(3ecGfJg GdYGde haj GdLRGFQs - (3UGdM(B, (3ehghHs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2020)
(3JfGhd GdcGJH GdGbJUGO GdSjGMj hecGfJg aj GdYGde haj GdLRGFQ ef NdGd CQHYI aUhd QFjSjI cGdBJj(B: ((3eONd YGde ddSjGMI hJaGYdgG eY GdeMjW, eaghe GdSjGMI GdOhdjI hecGfJgG aj GdGbJUGO GdYGdej, JTNjU deQGMd JWhQ GdSjGMI GdLRGFQjI hdhVYjJgG GdMGdjI,haj GdCNjQ bOe ebJQMGJ dJfejI GdSjGMI GdLRGFQjI Ydi GdeOi GdWhjd(B) . s
(3GdeQGLY U(B.211s
Keywords: (3GdEbJUGO (B- (3GdSjGMI (B- (3GdLRGFQs